Beliefs about the Stock Market and Investment Choices: Evidence from a Survey and a Field Experiment - Laudenbach, Christine; Weber, Annika; Weber, Rüdiger; Wohlfart, Johannes (Review of Financial Studies, 2026)
Abstract We survey retail investors at an online bank to study how beliefs about the autocorrelation of aggregate stock returns shape investment decisions measured in administrative account data. Individuals’ beliefs exhibit substantial heterogeneity and predict trading responses to market movements. We inform half of our respondents that, historically, the autocorrelation was close to zero, which causes them to update their perceived current autocorrelation and return expectations. The treatment shifts respondents’ equity purchases during the COVID-19 crash months later in the direction implied by the intervention. Our results provide causal evidence about the drivers of disagreement and trade in asset markets.